PENERAPAN KERTAS SEMEN BEKAS DALAM STRUKTUR DESAIN KURSI DENGAN TEKNIK LAMINASI PIPA - Kristian Oentoro; Tosan Tri Putro (IST AKPRIND Yogyakarta, 2018)
The needs of cement in Indonesia are increasing along with infrastructure development in various regions in Indonesia. Based on data from the Ministry of Industry in 2017, national cement needs have reached 70 tons per year. One of the environmental impacts is a lot of cement stacks in various construction sites. Meanwhile, the thickness and the strength of cement paper is better than the other types of paper because it has gramatur up to 180 gsm, thus capable for packing a weight of 40kg or one sack of cement. The utilization of used cement paper into recycled material is a step to extend the use value and becoming environmentally friendly material. Based on previous research, the compaction of materials through laminated paper cement can be used as a combination of children's furniture and has a hardness value of 2.86 kg / mm2. Whereas in this study, the utilization of used cement paper waste aims to determine the potential for lamination applications in the form of used cement paper pipes as the main material in the chair structures design for adult users. Research and development of chair design adapted the form follows material method which through three main stages, namely identification, visualization and materialization. The results of this study showed that the application of used pipe paper laminated into the chair structure design was able to withstand 132 kg of user load with through connection techniques and the classification of furniture design forms were orthogonal.